PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA FISIK, DAN KOMPENSASI PADA KINERJA KARYAWAN UD.TERUS DI BALI - Yogi Antara, I Ketut Kusuma (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 9 Nomor 2 Tahun 2015)
The aims of  this study is to investigate the effect of leadership, physical work environment, and compensation on employee performance. The sample size was 91 employees of UD Terus in Bali which was determined by saturated sampling technique. Method of data gathering used was questionnaire distribution with five Likert’s Scale. Technique of analysis implemented in this study was multiple linear regression. The findings show that partially, leadership, physical work environment, and compensation has positive impact on performance. Additionally, 80.8 percent of employees performnace variation determined by leadership, physical work environment, and compensation, whereas 19.2 percent determined by other variables not considered in this study
Keywords: performance , leadership , physical work environment, compensation.